Tujuh Pembiasaan Akhlaq Disiplin dI Sekolah Berbasis Alam (Studi Kasus Di SMP Sanggar Anak Alam Nitiprayan Kasihan Bantul Yogyakarta) - Ahmad Dwi Nur Khalim (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
Discipline is an action that shows orderly behavior and is compliant with a rule or norm. Compliance or obedience to the rule system in life, will not feel heavy if done consciously. The attitude of the discipline becomes light if it is carried out together. Discipline Akhlak become an individual's hopes and dreams. No exception is the expectations of teachers to students, parents to children, leaders to employee. This study uses field research with descriptive-qualitative data types. The results of this study indicate that the habitual discipline in Sanggar Anak Alam School (SALAM) has been going well. There are supporting factors and there are inhibiting factors in the discipline of moral discipline in the Sanggar Anak Alam School (SALAM)